Creative industry: its involvement in business world - Ab. Aziz Shuaib; Olalere, Folasayo Enoch (2013)
Creative industry involves the exploration of intellectual properties such as knowledge and tangible products which have potential of creating wealth and job. Therefore, design and heritage that makes-up the creative industry is believed to have great influence on the economy wellbeing of businesses. In the light of this, this paper seeks the knowledge regarding design and heritage, areas where they have been widely used, and also the kind of brain needed to be a good creative designer. Finally, the paper illustrates the involvement of creative industry in business world, using the tourism and hospitality business as the case study.